PENGARUH PEMBELAJAN BERBASIS MASALAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MAHASISWA - Fatimah Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study aims to determine the effect of Problem Based Learning on the mathematical problem solving ability of students.The sample used in this study was taken from 67 students from semester VII in mathematics department FKIP at University of Al Asyariah Mandar which were divided into two classes. The data was collected by using an observation sheet, achievement test, and students’ questionnaire responses to a problem Based Learning model. Descriptive analysis showed that the average result in problem-solving ability in control class was 55.99% to 69.73%; While in experimental class was 60.40% to 88.16%.The results of the students were in the ideal category and 80% of the students gave a positive (happy) response towards the applied of learning model. Based on normalised gain analysis obtained, the gain for the experimental group was 0.861 (in the high category), while the control group was 0.294 (located in the lower category). Inferential analysis showed that there was a significant difference between the two classes, the class tasked with the problem-based learning model had positive results and this model was more effective in improving the mathematical problem solving ability of students.